The Persistence of Extractive Sector Dominance and Development Policies in the Border Islands: A Circular and Cumulative Causation Approach in Natuna Regency - Luthfi Sultan; Bhimo Rizky Samudro; Albertus Maqnus Soesilo; Yogi Pasca Pratama; Andri Prasetyo; Muhammad Bagus Sistriatmaja (JURNAL ECONOMINA, 2026)
Natuna Regency is a resource-rich island border region, but its economy is concentrated in the weakening extractive sector. This study explains the persistence of this sector's dominance by integrating sectoral structure analysis and policy analysis into the Circular and Cumulative Causation (CCC) framework. The study uses an explanatory case study approach based on secondary data, with Location Quotient, Shift-Share, and Klassen Typology analysis for the 2015–2024 GRDP structure; content analysis of Presidential Regulation 41/2022 and Natuna Regent Regulation 16/2024; and analysis of fiscal data (Oil and Gas Revenue Sharing Funds and expenditure allocations) for the 2020–2024 period as an empirical bridge. The results show that the Mining and Quarrying sector contributed an average of 71.90% of GRDP but grew negatively (CAGR -1.02%), while the Agriculture, Forestry, and Fisheries sector was the only diversification candidate that consistently strengthened. Formal policy commitments to fisheries are categorized as symbolic because they are not accompanied by fiscal reallocation: the proportion of Fisheries Service spending is only 0.81–1.34% and its gap with the weight of GRDP actually widened after the policy was enacted. Fiscal dependence on Oil and Gas DBH, which consistently exceeds PAD (a ratio of 171–352%), indicates a vicious cycle mechanism with dominant backwash effects. The study recommends earmarking Oil and Gas DBH for diversification, operational translation of national mandates, and optimization of PAD as an integrated intervention package